Analisis Penataan Lingkungan Main Indoor yang Mendukung Kemampuan Problem Solving pada Anak - Salma Azzah Azahra Zein; Muniroh Munawar; Nila Kusumaningtyas (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The low ability of problem solving in children requires stimulation efforts in early childhood education, one of which is through the management of the maximum play environment that educators can do in optimizing problem solving abilities in children.  The problem in this study is about the implementation of learning with a play environment that raises problem solving abilities in children aged 5-6 years.  This research was conducted at the Center of Excellence Paud Taman Belia Candi, Semarang City.  This type of research is qualitative research in descriptive form.  Researchers use a naturalist approach, namely the presence of researchers directly in the field.  This study discusses the analysis of indoor play environment that supports problem solving abilities in children aged 5-6 years.  The results showed that the problem-solving ability of children aged 5-6 years could be improved through structuring the play environment in such a way as that at the Center of Excellence PAUD Taman Belia Candi Semarang.  In order for children to achieve maximum development in the aspects of cognitive development in the scope of problem solving development, it is necessary to organize an environment that stimulates or invites children (inviting classroom), facilitates multi-sensory children and provides opportunities for activities for children.  Based on the results of this study, the suggestion that can be conveyed is that in each learning process, the teacher can add knowledge and skills in arranging the indoor learning environment through various sources so that the center room is arranged in an optimal state for the learning process.